Herb and Spices in Colorectal Cancer Prevention and Treatment: A Narrative Review - Hossain, Md. Sanower; Kader, Md. Abdul; Goh, Khang Wen; Islam, Maidul; Khan, Md. Sharif; Harun-Ar Rashid, Md.; Ooi, Der Jiun; Melo Coutinho, Henrique Douglas; Al-Worafi, Yaser Mohammed; Moshawih, Said; Lim, Ya Chee; Kibria, K. M. Kaderi; et al. (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is the second most deadly cancer worldwide. CRC management is challenging due to late detection, high recurrence rate, and multi-drug resistance. Herbs and spices used in cooking, practised for generations, have been shown to contain CRC protective effect or even be useful as an anti-CRC adjuvant therapy when used in high doses. Herbs and spices contain many bioactive compounds and possess many beneficial health effects. The chemopreventive properties of these herbs and spices are mainly mediated by the BCL-2, K-ras, and MMP pathways, caspase activation, the extrinsic apoptotic pathway, and the regulation of ER-stress-induced apoptosis. As a safer natural alternative, these herbs and spices could be good candidates for chemopreventive or chemotherapeutic agents for CRC management because of their antiproliferative action on colorectal carcinoma cells and inhibitory activity on angiogenesis. Therefore, in this narrative review, six different spices and herbs: ginger (Zingiber officinale Roscoe), turmeric (Curcuma longa L.), garlic (Allium sativum L.), fenugreek (Trigonella foenum-graecum L.), sesame (Sesamum indicum L.), and flaxseed (Linum usitatissimum L.) used in daily cuisine were selected for this study and analyzed for their chemoprotective or chemotherapeutic roles in CRC management with underlying molecular mechanisms of actions. Initially, this study comprehensively discussed the molecular basis of CRC development, followed by culinary and traditional uses, current scientific research, and publications of selected herbs and spices on cancers. Lead compounds have been discussed comprehensively for each herb and spice, including anti-CRC phytoconstituents, antioxidant activities, anti-inflammatory properties, and finally, anti-CRC effects with treatment mechanisms. Future possible works have been suggested where applicable.